GUIDELINES FOR DEVELOPING SUMMER TRAINING FOR NOVICES ACCORDING TO THE 3 PRINCIPLES OF SADDHAMMA IN WAT PHRA DHAMMAKAYA - Visāratchayo (TrekulKusri), Phramahā Chatdanai; Jongsakulsiri , Padet; Sawaddi, Suthit (Journal of Educational Review Faculty of Education in MCU, 2024)
The purposes of this research article were 1) to study the conditions of summer novice training, 2) to study methods for developing summer novice training according to the principles of Saddhamma 3, and 3) to propose guidelines for developing summer novice training according to the 3 principles of Saddhamma in Wat Phra Dhammakaya. A sample group was novices in the summer novice ordination project for the year 2023, totaling 278, collected questionnaire data on their opinions on the conditions of summer novice ordination training. Use statistics to analyze frequency, mean, and standard deviation and analyzed content from interviews with 5 key informants. The research results found that: 1) Conditions of summer novice training in overall, it was at a high level because the monks had activities to practice Dhamma during the summer session, to study and learn discipline in order to practice orderliness and to promote the learning of volunteerism in order to create a body of knowledge for novices who received training performed public service according to the priorities of the training activities. 2) Methods for summer training for novices according to the 3 principles of Saddhamma were as following: (1) Dhamma practice activities; knowledge of steps should be given before practicing meditation. (2) Discipline training; providing knowledge about discipline in dressing properly, getting up, walking, sitting, bowing, and worshiping. (3) Volunteer spirit; the monks should take novices to participate in activities with the community in order to learn about sacrifice. And 4) in the area of community service; should participate in service activities in the Dhammakaya Temple network and participated in community activities so that the novices who attend the training could see the value of volunteerism. 3) Guidelines for summer novice training according to the principle of the 3 Noble Truths were as following: The first aspect: Dhamma practice activities (1) Pariyatti-saddhamma: includeing activities such as chanting, praying, and meditating. (2) Paṭipatti-saddhamma: includeing morning and evening prayers, sitting meditation, and walking meditation as learning activities. (3) Paṭivedha-saddhamma: should test the practice of morning and evening prayers and testing the mood of meditation. The second aspect: Discipline training (1) Pariyatti-saddhamma: providing knowledge about the conduct of monks and novices, especially the 10 precepts, keeping the 10 precepts, and the matter of proper clothing for monks, receiving food when receiving alms, and eating. (2) Paṭipatti-saddhamma: should wear proper clothing, and daily routine conduct. (3) Paṭivedha-saddhamma: letting the novices who attend the training in wearing robes and taking the 10 precepts. The third aspect was volunteerism: (1) Pariyatti-saddhamma; must be trained to learn about volunteerism from role models who were volunteers in the community, let them learn the methods of volunteerism. (2) Paṭipatti-saddhamma; cleaning the temple area and participating in community activities. (3) Pariyatti-saddhamma; knowing and realizing the benefits of volunteerism, having responsibility and sacrifice, having self-discipline in living with society and devoting oneself to the benefit of the public. The fourth aspect was community service: (1) Pariyatti-saddhamma; learning discipline, training in mind management and teamwork. (2) Paṭipatti-saddhamma; knowing how to plan work together, having generosity and be in a cheerful mood. (3) Pariyatti-saddhamma; resulting of working as a team, generosity, being a good citizen of society and living in society happily.